Frontiers of stem cell engineering for nanotechnology-mediated drug delivery systems - Serap Yeşilkır Baydar; Hatice Feyzan Ay; Rabia Cakir Koc (International Association of Physical Chemists (IAPC), 2024)
Background and purpose: Cell biology approaches have gained a successful integration, development and application of nanotechnology with stem cell engineering and have led to the emergence of a new interdisciplinary field known as stem cell nanotechnology (SCN). Recent studies showed the potential and the advancement of developments for SCN applications in drug delivery systems. Cancer, neurodegenerative, muscle and blood diseases, cell and gene therapies, and tissue engineering and regenerative medicine applications are the important targets of SCN. Experimental approach: In this overview, we searched the literature using the common online websites for research and read the open access, full-text available articles since 2013. Key results: The studies vary according to the type of disease they targeted and the strategies they proposed, whether diagnostic or therapeutic. In addition to the use of stem cells, the utilisation of their membranes, secretomes, exosomes and extracellular vesicles with an appropriate nanotechnology strategy is also an aspect of the research. Conclusion: This brief overview of stem cell nanotechnology over the last ten years aims to provide insight into the frontiers of stem cell engineering for nanotechnology-mediated drug delivery systems.